Requirements and Classification of Ijma’ in Legal Studies - Rahmawati, Artifah Tomi; Azdania, Hanifa; Apriantoro, Muhamad Subhi (Global Research Network, 2024)
This study delves into the requirements and classifications of Ijma’ (consensus) in the context of Islamic legal studies. As a source of Islamic law, Ijma’ has long been a focal point in the development of Islamic jurisprudence. However, clarity regarding the prerequisites for the validity of Ijma’ and its categorization in various contexts remains a subject requiring further investigation. This research identifies and analyzes the qualifications necessary for Ijma’ to be considered valid, including the criteria for scholars' consensus, alignment with primary sources of Islamic law, and its relevance to Islamic legal principles. Additionally, the study explores the understanding and application of Ijma’ classifications within temporal frameworks, social contexts, and modern-day relevance. The study relies directly on texts or data rather than events or empirical data. The researcher engages exclusively with existing sources or data available in libraries. By employing a qualitative research method and a library research approach, this study contributes to a deeper understanding of the requirements and classifications of Ijma’ in Islamic law, as well as its implications for legal decision-making. The findings of this research aim to enrich the discourse on the role of Ijma’ as a legitimate and relevant source of law while solidifying its position in legal decision-making. The implications of this study pave the way for further discussions on the dynamics of Ijma’ in addressing contemporary challenges.